Milton Civic Center Design: Envisioning a Focus of Community Life. - Krane, Anna; Shen, Yaqi.; Sullivan, Evan. (Tufts University. Tisch Library., 2018)
2015 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Milton Planning Department.